Food Safety Management System di Hotel Resort Area Kabupaten Garut - R. Sondjana Ali Suganda; R. Darmawan Sundayana; Hery Soesanto; Kusherdyana Kusherdyana; Syaeful Muslim (STIEPAR YAPARI Bandung, 2020)
The purpose of this study was to determine the procedure for receiving perishable raw materials at the Resort Hotel area of ??Garut Regency and understand the application of the Food Safety Management System on the receiving area for perishable raw materials at the Resort Hotel area of ??Garut Regency. The method used in this study is a qualitative method. The object of this research was carried out in a number of Resort Hotels in the Garut Regency area. The sampling technique in this study was carried out using purposive sampling method. The data collection technique was carried out by in-depth interviews with the receiving sections at each hotel in Garut district (Dariza Resort, Sumber Alam Resort, Kampung Sampireun Resort, Sabda Alam Resort). Direct observations were made on each receiving process at each hotel area in Garut district. The data collection tool was carried out by means of a checklist as well as an interview guide. The results showed that the receiving process in the hotel area of ??Garut Regency was quite good but there were still deficiencies in the application of the receiving process in terms of the procedure for receiving perishable food raw materials, delivery from suppliers to food raw material receiving officers did not have chiller or coolers and did not provide labeling. or food container stamp with the date it was received.